Social Sensing: An Exploratory Investigation for Smart City (International Journal of Engineering and Computer Science, 2015)
In the era of information technology, Social sensing [1][3] is a latest useful technology for collecting theinformation which is directly associated with the human and other social resources. Most common example of socialsensors are smart phones( mobile), in the smart phone , there exists many in-built sensors like GPS, Bluetooth, Wi-Fi andother location finding apps, temperature mapping sensors. The sensor are not used only in mobiles but also in automobilesvehicles like Bus, Car, Oven, Television, microwave etc. in smart kitchen to make smart home. The main concept is tomake knowledge based society and intelligent system on the national and international level. Smart city is todays as well asfuture demand in the modern society for every country to arrange and run the social system in proper, efficient andeffective manner. In this paper, the efforts have been made for various aspects of a smart city design and Implementation.